Urban Public Spaces From Planned Policies to Everyday Politics (Illustrated with Brazilian Case Studies) (The Urban Book Series,, 2018)
This book is about understanding, contextualizing and carrying out critical analyzes of the policies intended and/or implemented by the various public and private actors in urban public spaces, as well as the daily, or eventual, politics exercised by the organized civil society and by citizens. It presents a collection of contributions about the public space in different theoretical, conceptual and methodological approaches. Coming from different disciplines, the authors share an understanding about the need to analyze the uses and appropriations of the city by social subjects and groups as they represent difference and see the city as a place to share life experiences; as such, they argue, through their cases studies, that places of public use should be thought of and understood as concept and as social practice. As an analytic tool, the book offers a five-dimension model to explore how people relate to daily life activities and confront imposed inequalities in their meeting places, how they engage in individual and collective manifestations and/or how they symbolically appropriate public spaces in face of the late capitalism led by large corporations and globalization. Together the authors seek to contribute to a city of utopia, where all differences can be seen and dealt with in public spaces and where free individuals can present themselves and engage in a vita activa.